Thermoelastic interactions in Al-n-Si-Ni structures at pulse laser irradiation - Vorobets, G.I.; Vorobets, M.M.; Fedorenko, A.P. (Functional Materials, 2005)
Using the scanning electron microscopy and optical metallography, the formation and redistribution of structural defects in the near-contact silicon layer of thermally untreated Al-n-Si structures resulting from thermoelastic stresses developed under pulse laser irradiation have been investigated experimentally. A structurized transition layer has been found to be formed at the metal/semiconductor interface at relaxation of elastic stresses in the metal layer. To explain the behavior features of the defect systems at the periphery of Schottky diodes under irradiation of Al-n-Si structures through a silicon optical window, a physical model of the laser radiation effect on the metal/semiconductor contact has been proposed taking into account temperature dependence of the radiation absorption coefficient in the semiconductor. Методами растровой электронной микроскопии и оптической металлографии экспериментально исследовано процессы формирования и перераспределения структурных дефектов в приконтактном слое кремния термически неотожженных структур AI—п— Si вследствие проявления термоупругих напряжений при импульсном лазерном облучении. Обнаружено формирование структурированного переходного слоя на границе металл-полупроводник при релаксации упругих напряжений в металлизации. Для объяснения особенностей поведения систем дефектов по периметру диодов Шоттки при облучении структур AI-п-Si через кремниевое оптическое окно предложена физическая модель воздействия лазерного излучения на контакт металл-полупроводник, учитывающая температурную зависимость коэффициента поглощения излучения в полупроводнике. Методами растрової електронної мікроскопії та оптичної металографії експериментально досліджено процеси формування та перерозподілу структурних дефектів у при-контактному шарі кремнію термічно невідпалених структур Al-n-Si внаслідок прояву термопружних напруг при імпульсному лазерному опроміненні. Виявлено формування структурованого перехідного шару на межі метал-напівпровідник при релаксації пружних напруг у металізації. Для пояснення особливостей поведінки систем дефектів на периметрі діодів Шотткі при опроміненні структур через кремнієве оптичне вікно запропоновано фізичну модель впливу лазерного проміння на контакт метал-напівпровідник, яка враховує температурну залежність коефіцієнта поглинання випромінювання у напівпровіднику.